Polyaniline-coated foam electrodes for electroencephalography (EEG) measurement. Issue 3 (3rd March 2016) - Muthukumar, N.; Thilagavathi, G.; Kannaian, T.
Abstract : In this research, textile electrode was developed using electrically conductive polyurethane (PU) foam for electroencephalography (EEG) biopotential measurements. The conductive PU foam was developed through coating of inherently conductive polyaniline (PANI) polymer on PU foam. The conductive PU foam was characterized for surface physical morphology by scanning electron microscope, chemical changes through EDX measurements, and surface resistance and impedance values through two probe resistivity measurement method. The conductive PU foam showed a surface resistance and impedance values of 7 KΩ/square and 1.45 MΩ, respectively. EEG measurements using hospital equipment revealed that the conductive PU foam electrode yielded results similar to commercial Ag/AgCl electrodes. Hence, this study reveals that the conductive PU foam electrode would be a feasible candidate for EEG measurements, particularly for continuous monitoring purposes.